Identification of a Novel Regulatory Gene, trmE, that Orchestrates Salmonella Flagellar Synthesis and Virulence - Haoyu Geng; Linyan Luo; Jian Zhang; Jingying Gao; Shizhong Geng; Paul Barrow (Microorganisms)
It is well established that flagella play a critical role in bacterial motility and virulence, and the genes associated with flagellar synthesis and regulation have been extensively characterized. In this study, we identified the trmE gene as a novel modulator of flagellar synthesis in Salmonella Enteritidis. A transposon (Tn5) mutant library of Salmonella Enteritidis (SE) was constructed through bacterial conjugation, followed by screening for motility-deficient mutants. Among 1321 mutants screened, C50041trmE::Tn5 exhibited reduced motility. To validate this phenotype, we constructed C50041ΔtrmE mutants and complementary strains C50041ΔtrmE::trmE. Compared to parental strain SE(C50041), C50041ΔtrmE displayed significantly lower mRNA levels of flagellar synthesis-related genes as determined via quantitative real-time PCR and the few visible flagella observed via transmission electron microscopy (TEM). Function studies assessing virulence also showed results that matched this phenotype; specifically, C50041ΔtrmE demonstrated decreased adhesion and invasion capabilities towards macrophages. Furthermore, C50041ΔtrmE induced impaired apoptosis and pyroptosis in macrophages, while exhibiting reduced mortality in BALB/c mice along with diminished mRNA levels of pro-inflammatory cellular factors within murine spleen. This study provides compelling evidence that the trmE gene in Salmonella Enteritidis is involved in flagellar synthesis.